À la recherche de la liberté perdue : le périple libérateur de Kenza dans Des rêves et des assassins de Malika Mokeddem - Nadia Khemiri (Multilinguales)
This article focuses on Malika Mokeddem’s novel Des Rêves et des assassins, in which the narrator tells the story of Kenza : a young girl who lived since childhood in an eliminatory society based on male favouritism. A whole narrative framework is traced around this feminine figure, who knew how to free herself and trace her path of liberation and accomplishment.